Treponema pallidum subsp. pertenue Displays Pathogenic Properties Different from Those of T. pallidum subsp. pallidum - Wicher, Konrad (American Society for Microbiology, 2000)
The present study described the susceptibility of C4D guinea pigs to cutaneous infection with Treponema pallidum subsp. pertenue Haiti B strain. The general manifestations of the disease in adults and neonates differ, to a certain degree, from those induced by T. pallidum subsp. pallidum Nichols strain. Noticeable differences between the infections were reflected in the character of the skin lesions, their onset and persistence, and the kinetics of the humoral response. The incidence and dissemination of cutaneous yaws lesions in very young guinea pigs were remarkably different from the low frequency observed in a similar age group of syphilis infection, 100 versus 17%, respectively. Moreover, as opposed to T. pallidum subsp. pallidum, T. pallidum subsp. pertenue does not cross the placenta. Offspring born to yaws-infected mothers did not produce immunoglobulin M antibodies and their organs, examined by PCR and rabbit infectivity test (RIT), were all negative. Examination of a large number of tissues and organs in adult, neonate, and maternal yaws by PCR and RIT clearly demonstrated that, unlike syphilis, there was a low incidence and short persistence of the yaws pathogen in internal organs. These findings stress the dermotropic rather than the organotropic character of yaws and provide further evidence of distinctive biological and pathological differences between yaws and venereal syphilis.